Some observations concerning sp and ure-2 in Neurospora - F. J. Bowring; David E. A. Catcheside (Fungal Genetics Reports, 1994)
We are currently seeking rec-2 which is proximal to am on linkage group V and are gleaning incidental information on genes in this region and elsewhere. So far, the following is apparent: sp is recessive: each of 15 heterokaryons forced between his-3 K874; sp B132 and am1 32213 strains by growth on Vogel's + glycine medium had wild-type morphology.